Кудрявая лысина: [юмористические рассказы] / Владимир Мальцев - Мальцев Владимир Энгельсович (Стринг, 2009)
Экземпляры: 1 (20160414) / Инвентарный номер: 53751 / Сис.шифр: Р2 / Авт.знак: М-21 / ББК: 84